USING DATA WAREHOUSE TO MANAGE HEALTH FACILITY DATA - Kamsuriah Ahmad; Hammad Fahli Sidek (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Managing a complete master list of public health facility data is deemed important in coordinating and planning of health services and achieving better service delivery. The master lists allow stakeholders to share a uniform operational health services data and ensuring availability and reliable data. This will able to support and manage patients clinical data and other health management services such as disease monitoring, facility management and monitoring service performance. However, most health facilities do not have accurate and informed data, this can affect monitoring of infrastructure and services provided. Various facilities have multiple and redundant lists of health data, the lists differ not only in the information they contain but also in the way they are named and identified. Existing studies state that the development of health facility registries store information mostly using conventional two-dimensional table methods or relational databases as in the case at the Health Informatics Center (HIC), Ministry of Health Malaysia. Hence, they faces the challenges in managing the data since it contains diverse data sources, the absence of uniform data standards and the dependence on manual processes and human intervention. To overcome the current problems, a dimensional modeling technique has been developed in an effort to design a Health Facility Data Warehouse. The proposed design of the data warehouse has been verified by the expert and they agrees that it is suitable for HIC to manage information related to health facilities due to its ability to deal with data sources, able to generate strategic information, as well as the ability to obtain a historical view of facility data. This study shows dimensional modeling techniques are effective in analyzing and designing data warehouse and can be a possible method in managing the master list of health facilities in Malaysia as well as other countries.